UPAYA PENINGKATAN LITERASI DIGITAL MELALUI SOSIALISASI PENGGUNAAN INTERNET SECARA SEHAT DAN CERDAS - Witi, Ferdinandus Lidang; Nena, Theresia Rosyelani; Pake, Kristinadia Putri; Bambur, Yosefina Septiriani; Seran, Clarita Ilona (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to enhance students' digital literacy by promoting healthy and responsible internet use at SMP Satu Atap Negeri 1 Soa, Ngada Regency, East Nusa Tenggara. The rapid development of information technology requires students not only to be passive users but also to be critical, ethical, and responsible digital citizens. The implementation method included interactive lectures, discussions, and hands-on practice in creating educational blogs. The activity was attended by 60 students and conducted in a face-to-face format. The results showed an increase in students’ understanding of data privacy, identifying misinformation, and the use of blogs as a creative and reflective learning medium. Moreover, integrating this activity with the school curriculum supports project-based learning approaches. Direct, in-person socialisation proved to be more effective in enhancing student engagement and comprehension compared to online methods. This program demonstrates that the right educational approach can foster digital awareness among students and serves as a foundational step in developing a digitally literate young generation. Future efforts may include follow-up training, development of digital learning modules, and active involvement of teachers and parents in supporting students' digital literacy journeys.